Til RvT 77, Tema-artikel: Med självbiografin som vapen. Peter Schindler och den katolska missionen i Danmark - Werner, Yvonne Maria (Religionsvidenskabeligt Tidsskrift, 2026)
English Abstract: This article examines the life and work of the Danish Catholic priest Peter Schindler through a biographical and microhistorical perspective. Particular attention is given to Schindler’s memoirs, written during his years at the German priestly college at Campo Santo Teutonico in Rome, where he lived from 1947 to the early 1960s. In these writings, Schindler portrays his residence in Rome as the fulfilment of a lifelong spiritual journey and as the culmination of a divine calling. However, contemporary sources reveal a more complex picture: his relocation to Rome was largely the result of strained relations with the Catholic leadership in Denmark and of earlier conflicts that had shaped his ecclesiastical career. By juxtaposing Schindler’s autobiographical narrative with other contemporary evidence, the article explores the tension between self-representation and historical circumstance and analyses broader issues concerning Catholic conversion, missionary activity, and the inculturation of Catholicism in Denmark. The study thereby demonstrates how a microhistorical approach to an individual life can illuminate wider processes within modern Catholic history. SVENSK RESUME: Denna artikel undersöker den danske katolska prästen Peter Schindlers liv och arbete i ett biografiskt och mikrohistoriskt perspektiv. Särskild uppmärksamhet ägnas åt Schindlers memoarer, skrivna under hans år vid det tyska prästkollegiet på Campo Santo Teutonico i Rom, där han bodde från 1947 till början av 1960-talet. I dessa skrifter skildrar Schindler sin vistelse i Rom som uppfyllandet av en livslång andlig resa och som kulmen på ett gudomligt kall. Samtida källor ger dock en mer komplex bild: hans förflyttning till Rom var till stor del ett resultat av ansträngda relationer med den katolska kyrkoledningen i Danmark och av tidigare konflikter som präglat hans kyrkliga karriär. Genom att ställa Schindlers självbiografiska berättelse mot andra samtida källor analyseras spänningen mellan självrepresentation och historiska omständigheter och analyseras bredare frågor kring katolsk konversion, missionsverksamhet och katolicismens inkulturering i Danmark. Studien illustrerar hur ett mikrohistoriskt perspektiv på en enskild persons livshistoria kan belysa bredare utvecklingslinjer i den moderna katolicismens historia.